PENINGKATAN KELARUTAN EKSTRAK ETANOL DAUN SIRIH MERAH (PIPER CROCATUM RUIZ & PAV.) MELALUI KOMPLEKSASI DENGAN β-SIKLODEKSTRIN - Yola Desnera Putri; Princesa Elnovita Tierra; Sohadi Warya; Adit Andriyannto (ASSYIFA : Jurnal Ilmu Kesehatan, 2026)
Red betel leaves (Piper crocatum Ruiz & Pav.) are rich in secondary metabolites, particularly flavonoids, which exhibit pharmacological potential such as antioxidant and antidiabetic properties. However, the low solubility of the extract poses a major challenge in drug formulation development. This study was designed to enhance the solubility of ethanol extract from red betel leaves by forming inclusion complexes with β-cyclodextrin using the kneading method, and further developing it into instant-dissolving granules. Extraction was performed via maceration technique with 70% ethanol as the solvent. Complexes were prepared by kneading at ratios of 1:1, 1:2, and 1:3 (extract:β-cyclodextrin). The resulting complexes were tested for solubility and formulated into granules through wet granulation. The extraction yielded 10.92% render. Kneading complex formation successfully increased solubility to 16.092% (F1), 27.844% (F2), and 36.302% (F3). Evaluation of the granules' physical properties showed parameters meeting standard requirements. The study concludes that β-cyclodextrin incorporation via kneading is effective in improving the solubility of red betel leaf extract and producing granules with optimal physical characteristics.